Never Off the Hook—How Fishing Subverts Predator-Prey Relationships in Marine Teleosts - Meekan, Mark G.; McCormick, Mark I.; Simpson, Stephen D.; Chivers, Douglas P.; Ferrari, Maud C. O. (Frontiers in Ecology and Evolution, 2018)
Although the behaviour of most organisms evolves in response to harvest, teleost fishes in marine systems have remained susceptible to the same basic fishing techniques of hook and lines and nets for millennia. We argue that this has occurred because these techniques circumvent the evolutionary arms race that exists between all other non-human marine predators and their fish prey that codifies effective tactics of foraging and predator evasion. By removing size relationships between predator and prey, avoiding predator recognition, disrupting learning cues and through the rapid evolution of technology, fishing by humans subverts and disrupts natural processes of selection on fishes that act to reduce mortality to non-human predators. This engenders high capture efficiency, allowing humans to become super-predators and explaining why non-human predators in marine systems are forced to focus on naïve and young individuals as prey, whereas humans are able to target adult fishes. Our very high rates of harvest and disruption of predator-prey relationships shifts the morphology and life history of target species towards traits (small adult size etc.) that are a disadvantage in situations where they must avoid non-human predators and thus has the potential to contribute to reduced resilience of fished populations and impair the recovery of stocks when harvesting ceases.